Comparative analysis of national and foreign players` performance in Euroleague Basketball - Paulauskas, R.; Kasparavicius, R.; Stumbras, M.; Figueira, B. (PLOS ONE, 2024)
This study aimed to quantitatively assess the statistical contributions between foreign and national players in men`s Euroleague Basketball. Data from 588 games in the 2021-2022 regular season and 612 games in the 2022-2023 regular season were analyzed through non-participant observation. Paired t-tests and Wilcoxon tests were employed to analyse variables with normal and non-normal distributions, respectively. The analysis indicated significant differences (p<0.05) between local and foreign players across several key variables, including Minutes, Points, Average Points, Usage Percentage, Individual Offensive Rating, Individual Defensive Rating, and True Shooting Percentage. These findings suggest pronounced distinctions between foreign players and national players concerning game volume indicators and game performance efficiency. Foreign players exhibited dominance in critical areas, such as playing time, total points scored, and average points per game, underscoring their substantial contributions to their respective teams. Consequently, these results offer practical implications for players, coaches, and fitness trainers, allowing for the design of more tailored training programs that account for distinct offensive and defensive needs, as well as the heightened physical demands experienced throughout the season.